Treatment of Rheumatoid Arthritis with Methotrexate Alone or A Combination of Methotrexate and Hydroxychloroquine - Natharubini Nadarajah; Riardi Pramudyo; Kuswinarti Kuswinarti (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Rheumatoid arthritis (RA) is an autoimmune disease that causes significant morbidity in most patients and also premature mortality in some. To prevent this, therapeutic approaches call for the early treatment of RA by using disease-modifying antirheumatic drugs (DMARDSs), either as single therapy or combination therapy. Although in the previous decade DMARDs were rarely used as combination, however now they are used widely to treat RA. The objective of this study was to compare the effectiveness of methotrexate (MTX) alone and the combination of MTX & hydroxychloroquine (HCQ) in RA patients.Methods: An analytic retrospective cohort study was conducted from May 2014 until October 2014, on 46 patients with RA in the rheumatology clinic of Dr. Hasan Sadikin General Hospital Bandung from January 2009−October 2014 who were taking MTX or MTX & HCQ for at least 1 year. The secondary data obtained from these patients’ medical record were then analyzed using the independent t-test and Mann-Whitney test.Results: The study showed that 93.48% of the patients were females. The mean change in disease activity measures were not significant for any of the parameter (p-value for SJC = 0.337; TJC = 0.676; ESR = 0.780). Also the comparisons of the disease activity score (DAS 28) before and after therapy was not significant (p-value = 0.584).Conclusion: There is no difference in the effectiveness of DMARD monotherapy with MTX and combination therapy with MTX & HCQ in RA patients.DOI: 10.15850/amj.v3n3.474